1997
DOI: 10.2514/2.5193
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Experiments of Laser-Induced Ignition of Nitramine Propellants

Abstract: The objective of the work is to develop and experimentally verify a model for CO 2 laser-induced ignition of nitramine-based propellants. The one-dimensional model considers heat conduction in the condensed-phase coupled to heat and mass transport with global chemical kinetics of a heterogeneous propellant in the gas-phase region. The highly nonlinear model was solved numerically. Experimentally, increases in heat ux [125 -375 W/cm 2 (193 -578 cal/s-in. 2 )] lowered the ignition delay time, but changes in pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The power meter, fitted with a 1 cm diameter mask, measured laser power incident on the pellet surface before each experiment. 5,15,20,[24][25][26][27] The predicted critical irradiance, I * , is presented in Fig. Table I with previously published experimental HMX laser ignition data.…”
Section: Laser Ignition Setupmentioning
confidence: 99%
“…The power meter, fitted with a 1 cm diameter mask, measured laser power incident on the pellet surface before each experiment. 5,15,20,[24][25][26][27] The predicted critical irradiance, I * , is presented in Fig. Table I with previously published experimental HMX laser ignition data.…”
Section: Laser Ignition Setupmentioning
confidence: 99%
“…Shu [12] studied the effect of surface area of am- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 monium perchlorate (AP), initial temperature, heat fluxes and catalyst on the ignition delay time of NEPE propellant within a CO 2 laser ignition system, and got the conclusions that AP acted as a kind of trigger during ignition and the effect of initial temperature on ignition delay time was influenced by heat fluxes. Wang [13] and Ritchie [14] analyzed the effect of laser heat flux on the ignition delay time of NEPE propellant, and found that the ignition delay time was exponentially related to laser heat flux. Xiang [15] discussed the influence of oxygen content in environment gas on the first flame position and ignition delay time of NEPE propellant, but did not study the ignition and combustion mechanism deeply.…”
Section: Introductionmentioning
confidence: 99%
“…The build-up of pressure following deflagration through laser heating is considered to give rise to a Shock-to-Detonation Transition (SDT) within the body of the charge. The kinetics of radiative transfer and its effect on energetic materials and pyrotechnics under laser irradiation have been modelled in the past by many researchers (6,7) .…”
Section: Introductionmentioning
confidence: 99%